(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT Coordination is an important function of government management. The purpose of this study was to determine how the implementation of the coordination function in governance in the sub Gemeh Talaud Islands. The method used is descriptive qualitative method. The informants who were interviewed as many as 12 people are: sub-district, sub-district secretary, Head of Unit Department / Agency (4), Head of Vertical Institutions (2), the village head (2), Leaders / Community Leaders (2). Data collection techniques used were interviews. Data was analyzed using qualitative descriptive analysis techniques-interactive model of Miles and Hubernann. Based on the results of the study conclude: 1. Coordination in the planning of programs / activities of governance among government agencies (Government of the District, SKPD and Agencies Vertical) in the District Gemeh is good enough, which is done through the forum district level coordination meeting led and coordinated by the Head, so as to realize the synchronization, harmony, harmony, balance, and overall integrity of the programs / activities of government. (2) Coordination in the implementation of programs / activities in the district administration Gemeh is good enough, namely through: district level coordination meetings; demand for and delivery of data / information or report on progress in the implementation of programs / activities of all SKPD and agencies existing vertical; and through monitoring / monitoring Head of the implementation of the program / activity. Based on the conclusions suggested: (1) There must be communication reciprocal harmony between the district governments (Head and his staff) with all the regional work units or SKPD (UPT Department / Agency and other work units), and Vertical Institutions in the region employment districts. (2) Head as the leader and coordinator of the sub-district government administration should seek to optimize the use of means of coordination such as coordination meetings, demand and delivery of data / information between all government work units in districts, and consulting. Keywords: Coordination, Government of the District.